Fault Detection Methods Suitable for Automotive Applications in Proton Exchange Fuel Cells - Barhate, S.; Mudhalwadkar, R.; Madhe, S. (Engineering, Technology & Applied Science Research, 2022)
The fault conditions degrade the performance of proton exchange fuel cells and reduce their useful life. The prolonged existence of a fault condition can permanently damage the fuel cell. This paper proposes four methods for fault detection and fault type isolation. These methods were based on the coefficient of variance, ratios of change in output power to change in voltage and change in output voltage to the change in current, fuzzy membership values and Euclidian distance, and wavelet transform. These methods are non-invasive to the fuel cell and involve non-destructive testing. These methods were experimentally validated.